A longitudinal examination of French and English reading comprehension in French immersion programs in Canada. (18th May 2022) - Bérubé, Daniel; Uchikoshi, Yuuko; Marinova-Todd, Stefka H.
Abstract: Parental level of education, instruction time, and amount of language practice that children receive have enhanced our understanding of how bilingual and multilingual children learn to comprehend text. Guided by the simple view of reading and the interdependence hypothesis, this longitudinal study conducted in Canadian French immersion programs examined the (a) within- and cross-language association between oral language skills and reading comprehension of bilingual English–French and multilingual children and (b) patterns of growth, while controlling for possible influences of parental level of education and methods of instruction on reading achievement. The sample included 150 children tested once at the beginning of Grade 4 (T1) and again at the end of Grade 4 (T2) and in Grade 6 (T3). Individual growth modeling revealed that bilingual and multilingual children showed similar development in oral language and reading skills across the timeframe. Moreover, growth in English and French reading comprehension was associated with within-language variables. English reading comprehension in Grade 4 was also associated with cross-language variables, including French listening comprehension and vocabulary knowledge. Reading development in the second and third language is enhanced in contexts where classroom instruction, as well as social, economic, and educational opportunities to learn, is equivalent for all students.